High-stability transition metal phosphide hydrogen evolution catalyst and preparation method thereof

By constructing a bifunctional metal phosphine-oxygen protective layer on the surface of the transition metal phosphide catalyst, the problem of taking into account both the stability and activity of the catalyst is solved, and the stability and activity of the catalyst is achieved, and it is suitable for a variety of electrochemical reactions.

CN119121300AActive Publication Date: 2024-12-13NORTHEAST GASOLINEEUM UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410939883.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2024-12-13
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

The poor durability of the transition metal phosphide catalyst makes it difficult to take into account both stability and activity during electrolytic hydrogen analysis. The existing protective layer design has problems of uneven thickness and unsolid bonding.

Method used

By constructing a bifunctional metal phospho-oxygen compound protective layer on the surface of the catalyst, using the phosphide active phase and NixCoyPzOh protective layer, a heterostructure is formed to improve the stability and activity of the catalyst, using foam nickel-supported metal precursor, hydrothermal reaction and phosphorus Catalysts are prepared by chemical treatment and other methods.

Benefits of technology

The dual improvement of the catalyst is achieved, which not only improves its stability in the electrolyte, but also enhances the catalytic activity. The protective layer and the catalyst are bonded through chemical bonds, and the uniformity and firmness are guaranteed, which are suitable for a variety of electrochemical reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121300A_ABST
    Figure CN119121300A_ABST
Patent Text Reader

Abstract

The invention relates to a high-stability transition metal phosphide hydrogen evolution catalyst. The catalyst is composed of a phosphide active phase and a bifunctional metal phosphorus oxide protective layer. The invention also relates to a preparation method of the high-stability transition metal phosphide hydrogen evolution catalyst, which comprises the following steps: firstly, loading a metal precursor on foamed nickel, and phosphating to obtain a phosphide catalyst; and then carrying out catalyst surface treatment to obtain the phosphide hydrogen evolution catalyst with a phosphorus oxide protective layer. The protective layer on the surface of the phosphide catalyst is a dual-function protective layer capable of improving activity and stability at the same time, the protective layer with controllable thickness and uniformity can be obtained through regulation and control of surface treatment conditions in the preparation process, the preparation process is simple, the cost is low, and the phosphide catalyst has important industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrocatalysis and energy materials, and relates to a high-stability transition metal phosphide hydrogen evolution catalyst and a preparation method thereof. Background Art

[0002] In order to meet the large-scale development of hydrogen production by electrolysis of water in industry, it is very important to further develop efficient and stable electrocatalysts to achieve overall water decomposition. In recent years, a lot of research has been done at home and abroad to improve the stability of electrocatalysts, mainly including modifying carbon materials or using other functional materials as catalyst carriers. Invention patent CN200710157375.9 discloses "a method for improving the stability of fuel cell catalysts", which improves the stability of carbon carriers by high-temperature treatment of carbon carriers to make them graphitized, and further improves the stability of catalysts. Invention patent CN103413951A prepares N-doped graphene-supported Pt alloy catalysts by introducing N-methylpyrrolidone as a N source during the preparation process, which improves the stability of the catalyst to a certain extent. Invention patent CN102945970A coats a nitrogen-carbon layer of a certain thickness on the surface of a metal oxide nanotube carrier by carbonizing a nitrogen-carbon source, thereby improving the stability and conductivity of the carrier. Invention patent CN 109994748B improves the stability of nano-electrocatalysts by doping N in carbon-supported precious metal nano-electrocatalysts. However, the preparation processes of these materials are relatively complicated, costly and energy intensive.

[0003] The most studied catalysts for hydrogen evolution in water electrolysis are transition metal borides, carbides, nitrides, sulfides, phosphides, selenides, etc. Among them, transition metal phosphides (TMPs) have attracted extensive attention due to their high natural abundance, low cost, and stable catalytic performance. TMPs are a general term for binary, ternary, and multi-element phosphides formed by phosphorus and transition metal elements (such as Fe, Co, Ni, Cu, Mo, W, etc.), generally with M x P y Said. TMPs are considered by researchers to be one of the most promising options to replace precious metal-based catalysts due to their unique electronic structure and excellent HER and OER catalytic performance. However, their poor durability limits their further large-scale application. Designing a protective layer for the catalyst is an effective strategy to improve its stability, but how to achieve uniformity and firmness of the protective layer thickness is the key. Due to the uneven thickness of the protective layer, local corrosion will occur, affecting the stability of the catalyst; if the protective layer is not firmly bonded to the catalyst, it is easy to fall off and lose its protective effect on the catalyst. The commonly used deposition method is to coat the surface of the catalyst with a metal oxide (such as MnO x), which plays a role in protecting the catalyst. However, this protective layer often affects the diffusion of the electrolyte, resulting in reduced catalyst activity; in the electrolyte environment, the protective layer formed by the deposition method is not firmly bonded to the catalyst and is easy to fall off, losing its protective effect. Therefore, it is particularly important to develop a protective layer that can simultaneously improve the electrocatalytic activity and stability to achieve a win-win situation for catalyst activity and stability, but catalysts with such a "dual-function" protective layer design are rarely reported. Summary of the invention

[0004] The first purpose of the present invention is to provide a high-stability transition metal phosphide hydrogen evolution catalyst, which overcomes the problem of poor stability of current transition metal phosphide catalysts by constructing a "dual-function" protective layer on the surface of the catalyst to improve the electrocatalytic activity and stability.

[0005] The second object of the present invention is to provide a method for preparing the above-mentioned high-stability transition metal phosphide hydrogen evolution catalyst.

[0006] The present invention is achieved through the following technical solutions: 1. A high-stability transition metal phosphide hydrogen evolution catalyst, which consists of a phosphide active phase and a bifunctional metal phosphorus oxide protective layer.

[0007] 2. According to the above-mentioned preparation method of high-stability transition metal phosphide hydrogen evolution catalyst, firstly, a metal precursor is loaded on nickel foam and phosphated to obtain a phosphide catalyst; then the catalyst surface is treated to obtain a phosphide hydrogen evolution catalyst with a phosphorus oxide protective layer.

[0008] Furthermore, the specific steps of the method are as follows: (1) The nickel foam was treated with 1 mol∙L -1 acetone, hydrochloric acid solution and deionized water, and dried for later use; (2) Mixing a Ni source and a Co source with NH4F, urea and deionized water to form a uniform solution, wherein the molar ratio of Co to Ni is 1-2:1, the molar ratio of NH4F to Co is 4-8:1, the molar ratio of urea to Co is 10-20:1, and the molar ratio of Co to deionized water is 0.001-0.002:1, transferring the solution to a reactor containing a vertically placed nickel foam, performing a hydrothermal reaction at 120-160° C. for 6-12 hours, cooling to room temperature, washing the solution alternately with ethanol and deionized water for 3 times, and drying the solution to obtain a catalyst precursor; (3) The catalyst precursor and P source were placed in two quartz boats respectively, with the molar ratio of P source to Ni source being 3-6:1. The quartz boats were then placed in a tube furnace and phosphated at 350 °C for 2 h in an inert gas atmosphere at a heating rate of 2 °C∙min. -1 , phosphating treatment is performed to obtain a NiCoP hydrogen evolution catalyst; (4) After the temperature of the tube furnace is lowered to 50-100°C, the air valve is opened and the oxygen content in the inert gas is adjusted to 0.5-10v%, and the treatment time is 1-2 hours. The temperature is lowered to room temperature to obtain NiCoP@Ni x Co y P z O h Hydrogen evolution catalyst.

[0009] Furthermore, the Ni source is any one of nickel chloride, nickel nitrate and nickel acetate.

[0010] Furthermore, the Co source is any one of cobalt chloride, cobalt nitrate and cobalt acetate.

[0011] Furthermore, the P source is any one of ammonium hypophosphite and sodium hypophosphite.

[0012] Furthermore, in the step (4), the inert gas is N2 gas or Ar gas.

[0013] The positive effect of adopting the above technical solution is that the surface of the phosphide catalyst of the present invention has a dual-function protective layer to prevent the catalyst active phase NiCoP from directly contacting the electrolyte. x Co y P z O h The protective layer is relatively stable in the electrolyte environment and can significantly improve the stability of the catalyst. x Co y P z O h The multivalent, highly electronegative P atom can regulate the electronic structure and stabilize the reaction intermediates, so Ni x Co y P z O h The protective layer itself has good catalytic activity; secondly, Ni x Co y P z O h The protective layer can further improve the hydrogen evolution activity of the NiCoP catalyst by forming a heterostructure with the NiCoP active phase and interacting with electrons at the interface of the heterostructure. Therefore, the protective layer constructed by the present invention is a "dual-function" protective layer that can improve both activity and stability; the preparation process can obtain a uniform protective layer with controllable thickness by regulating the surface treatment conditions, and the preparation process is simple and low in cost. The in-situ grown protective layer is firmly bonded to the catalyst through chemical bonds and is not easy to fall off; the method can be widely used in a variety of important electrochemical reactions such as water decomposition, carbon dioxide reduction, and microbial fuel cells, and has important industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 NiCoP@Ni x Co y P z O h / NF catalyst preparation process; Figure 2 NiCoP@Ni x Co y P z O h / XRD pattern of NF catalyst; Figure 3 NiCoP@Ni x Co y P z O h TEM image of / NF catalyst; Figure 4 NiCoP@Ni x Co y P z O h / NF catalyst protective layer formation and characteristic diagram; Figure 5 NiCoP@Ni x Co y P z O h LSV curve of hydrogen evolution of / NF catalyst; Figure 6 NiCoP@Ni x Co y P z O h Stability curve of the / NF catalyst. DETAILED DESCRIPTION

[0015] The technical solution of the present invention is further described below in conjunction with specific embodiments, but it should not be construed as limiting the present invention. Example 1

[0016] The nickel foam was treated with 1 mol∙L -1acetone, hydrochloric acid solution and deionized water, and dried for use. Nickel chloride, cobalt nitrate, NH4F, urea and deionized water (the molar ratio of Ni, Co, NH4F, urea and deionized water is 1:1:8:10:1000) are mixed to form a uniform solution, which is transferred to a reactor containing a vertically placed nickel foam, and hydrothermally reacted at 120°C for 12 hours. After cooling to room temperature, it is washed alternately with ethanol and deionized water for 3 times, and dried to obtain a Ni-Co bimetallic precursor; the obtained precursor and ammonium hypophosphite are placed in two quartz boats respectively, and the molar ratio of ammonium hypophosphite to nickel chloride is 3:1. The quartz boat is then placed in a tube furnace and phosphated at 350°C for 2 hours in a nitrogen protective atmosphere, with a heating rate of 2°C∙min -1 , phosphating treatment was performed to obtain NiCoP / NF catalyst, the temperature was lowered to 100 °C, the oxygen valve was opened, and the oxygen content in nitrogen was adjusted to 10v%. After surface treatment for 1h, the temperature was lowered to room temperature to obtain NiCoP@Ni x Co y P z O h / NF catalyst (see Figure 1 ).

[0017] The NiCoP@Ni obtained in this example x Co y P z O h / NF catalyst XRD characterization: The obtained NiCoP@Ni x Co y P z O h / NF catalyst was characterized by XRD and the active phase in the catalyst was analyzed and tested. The results showed that (see Figure 2 ), the characteristic peaks at 2θ = 44.5°, 51.9° and 76.5° belong to the (111), (200) and (220) crystal planes of nickel foam (PDF#70-0989). The characteristic peaks at 2θ = 40.9°, 44.9°, 47.3° and 54.4° belong to the NiCoP phase, which are the NiCoP (111), (201), (210) and (300) crystal planes (PDF# 71-2336), indicating that the active phase in the catalyst is NiCoP. Example 2

[0018] The nickel foam was treated with 1 mol∙L -1acetone, hydrochloric acid solution and deionized water, and dried for use. Nickel nitrate, cobalt nitrate, NH4F, urea, and deionized water (the molar ratio of Ni, Co, NH4F, urea, and deionized water is 1:1:4:20:500) are mixed to form a uniform solution, which is transferred to a reactor containing a vertically placed nickel foam, and hydrothermally reacted at 160°C for 6 hours. After cooling to room temperature, it is washed alternately with ethanol and deionized water for 3 times, and dried to obtain a Ni-Co bimetallic precursor; the obtained precursor and sodium hypophosphite are placed in two quartz boats respectively, and the molar ratio of sodium hypophosphite to nickel nitrate is 6:1. The quartz boat is then placed in a tube furnace and phosphated at 350°C for 2 hours in a nitrogen protective atmosphere, with a heating rate of 2°C∙min -1 , phosphating treatment was performed to obtain NiCoP / NF catalyst, the temperature was lowered to 50 °C, the oxygen valve was opened, and the oxygen content in nitrogen was adjusted to 0.5v%. After surface treatment for 2h, the temperature was lowered to room temperature to obtain NiCoP@Ni x Co y P z O h / NF catalyst.

[0019] The NiCoP@Ni obtained in this example x Co y P z O h TEM characterization of / NF catalyst: The obtained NiCoP@Ni x Co y P z O h The TEM characterization results of the / NF catalyst are shown in Figure 3 (a) A uniform protective layer is formed on the catalyst surface, with a thickness of about 4 nm. The active phase of the catalyst NiCoP is x Co y P z O h The protective layer forms a heterostructure. Example 3

[0020] The nickel foam was treated with 1 mol∙L -1acetone, hydrochloric acid solution and deionized water, and dried for use. Nickel acetate, cobalt acetate, NH4F, urea, and deionized water (the molar ratio of Ni, Co, NH4F, urea, and deionized water is 1:2:9:15:1000) are mixed to form a uniform solution, which is transferred to a reactor containing a vertically placed nickel foam, and hydrothermally reacted at 160°C for 6 hours. After cooling to room temperature, it is washed alternately with ethanol and deionized water for 3 times, and dried to obtain a Ni-Co bimetallic precursor; the obtained precursor and ammonium hypophosphite are placed in two quartz boats respectively, and the molar ratio of ammonium hypophosphite to nickel acetate is 4:1. The quartz boat is then placed in a tube furnace and phosphated at 350°C for 2 hours in a nitrogen protective atmosphere, with a heating rate of 2°C∙min -1 , phosphating treatment was performed to obtain NiCoP / NF catalyst, the temperature was lowered to 50 °C, the oxygen valve was opened, and the oxygen content in nitrogen was adjusted to 0.5v%. After surface treatment for 2h, the temperature was lowered to room temperature to obtain NiCoP@Ni x Co y P z O h / NF catalyst.

[0021] The NiCoP@Ni obtained in this example x Co y P z O h TEM characterization of / NF catalyst: The obtained NiCoP@Ni x Co y P z O h The TEM characterization results of the / NF catalyst are shown in Figure 3 (b) A uniform protective layer is formed on the catalyst surface, and its thickness is about 2 nm. It can be seen that the thickness of the protective layer can be regulated by regulating the surface treatment conditions. In addition, this protective layer, because MP is chemically bonded, the Ni x Co y P z O h It is obtained by directly inserting O into NiCoP on the catalyst surface, so it is very firmly bonded to the catalyst and is not easy to fall off, and forms a uniform coating, which plays a good protective role (see Figure 4 ). This indicates that the catalyst protective layer is firmly combined with the catalyst activity, the protective layer is uniform, and the thickness is controllable. Example 4

[0022] The nickel foam was treated with 1 mol∙L -1acetone, hydrochloric acid solution and deionized water, and dried for use. Nickel nitrate, cobalt nitrate, NH4F, urea, and deionized water (the molar ratio of Ni, Co, NH4F, urea, and deionized water is 1:1:5:15:500) are mixed to form a uniform solution, which is transferred to a reactor containing a vertically placed nickel foam, and hydrothermally reacted at 120°C for 6 hours. After cooling to room temperature, it is washed alternately with ethanol and deionized water for 3 times, and dried to obtain a Ni-Co bimetallic precursor; the obtained precursor and ammonium hypophosphite are placed in two quartz boats respectively, and the molar ratio of ammonium hypophosphite to nickel nitrate is 5:1. The quartz boat is then placed in a tube furnace and phosphated at 350°C for 2 hours in a nitrogen protective atmosphere, with a heating rate of 2°C∙min -1 , phosphating treatment was performed to obtain NiCoP / NF catalyst, the temperature was lowered to 50 °C, the oxygen valve was opened, and the oxygen content in nitrogen was adjusted to 5v%. After surface treatment for 2h, the temperature was lowered to room temperature to obtain NiCoP@Ni x Co y P z O h / NF catalyst.

[0023] NiCoP / NF catalyst was prepared for comparison: other conditions were the same as those of NiCoP@Ni x Co y O z The preparation method of / NF catalyst is the same as that of the catalyst, except that it is directly cooled to room temperature after phosphating.

[0024] The NiCoP@Ni obtained in this example x Co y O z Determination of hydrogen evolution catalytic activity of NiCoP / NF catalyst and NiCoP / NF without protective layer: In 1.0 M KOH solution, a typical three-electrode system was used to test the linear sweep voltammogram (LSV) to evaluate the hydrogen evolution reaction (HER) catalytic activity of the catalyst. Figure 5 .Depend on Figure 5 It can be seen that under alkaline conditions, the overpotential η of the NiCoP / NF catalyst is 10 =100 mV, NiCoP@Ni with protective layer x Co y O z The overpotential η of the catalyst 10 Only 54 mV, a decrease of 46%, indicating that the activity of the catalyst is further improved after adding the protective layer. The protective layer can improve the activity of the catalyst, which can be explained from two aspects. First, Ni x Co y P z O hThe multivalent, highly electronegative P atom can regulate the electronic structure and stabilize the intermediates of the hydrogen evolution reaction, thus having hydrogen evolution catalytic activity. x Co y P z O h The protective layer forms a heterostructure with the NiCoP active phase and can further improve the hydrogen evolution activity of the NiCoP catalyst through electronic interaction at the heterostructure interface. Example 5

[0025] The nickel foam was treated with 1 mol∙L -1 acetone, hydrochloric acid solution and deionized water, and dried for use. Nickel chloride, cobalt chloride, NH4F, urea, and deionized water (the molar ratio of Ni, Co, NH4F, urea, and deionized water is 1:1.5:8:20:1000) are mixed to form a uniform solution, which is transferred to a reactor containing a vertically placed nickel foam, and hydrothermally reacted at 120°C for 8 hours. After cooling to room temperature, it is washed alternately with ethanol and deionized water for 3 times, and dried to obtain a Ni-Co bimetallic precursor; the obtained precursor and sodium hypophosphite are placed in two quartz boats respectively, and the molar ratio of sodium hypophosphite to nickel chloride is 3:1. The quartz boat is then placed in a tube furnace and phosphated at 350°C for 2 hours in a nitrogen protective atmosphere, with a heating rate of 2°C∙min -1 , phosphating treatment was performed to obtain NiCoP / NF catalyst, the temperature was lowered to 50 °C, the oxygen valve was opened, and the oxygen content in nitrogen was adjusted to 5v%. After surface treatment for 2h, the temperature was lowered to room temperature to obtain NiCoP@Ni x Co y P z O h / NF catalyst.

[0026] NiCoP / NF catalyst was prepared for comparison: other conditions were the same as those of NiCoP@Ni x Co y O z The preparation method of / NF catalyst is the same as that of the catalyst, except that it is directly cooled to room temperature after phosphating.

[0027] The NiCoP@Ni obtained in this example x Co y O z Determination of hydrogen evolution catalytic stability of NiCoP / NF catalyst and NiCoP / NF without protective layer: In a 1.0 M KOH solution, the hydrogen evolution stability of the catalyst was evaluated by comparing the changes in the LSV curves after 3000 cycles of testing using a typical three-electrode system. The results are shown in Figure 6 (a). As can be seen from the figure, NiCoP@Ni x Coy O z The difference between the LSV curve of hydrogen evolution of NiCoP / NF catalyst and the initial state is much smaller than that of NiCoP / NF, indicating that the stability of the catalyst is improved after adding the protective layer. The results of the 65-hour constant current test are shown in Figure 6 (b). As can be seen from the figure, NiCoP@Ni x Co y O z The performance of the NiCoP / NF catalyst was stable and stable in the 65-hour constant current test, with a small performance decay. In contrast, the performance decay of the NiCoP / NF catalyst was more significant, with a clear downward trend. This further confirms that the protective layer can significantly improve the stability of the catalyst.

[0028] The phosphide catalyst of the present invention has Ni on its surface. x Co y O z Protective layer to prevent the active phase NiCoP of the catalyst from directly contacting the electrolyte. x Co y P z O h The protective layer is relatively stable in the electrolyte environment and can significantly improve the stability of the catalyst; therefore, combined with Example 4, Ni x Co y O z The protective layer has the dual function of improving the activity and stability of the catalyst at the same time, and is a "dual-function" protective layer. The preparation process can obtain a thickness-controllable and uniform protective layer by regulating the surface treatment conditions. The preparation process is simple and low-cost. The in-situ grown protective layer is firmly bonded to the catalyst through chemical bonds and is not easy to fall off. This method can be widely used in many important electrochemical reactions such as water decomposition, carbon dioxide reduction, and microbial fuel cells, and has important industrial application value.

Claims

1. A high stability transition metal phosphide hydrogen evolution catalyst, characterized in that: The catalyst consists of a phosphide active phase and a bifunctional metal phosphorus oxide protective layer.

2. The method for preparing a high stability transition metal phosphide hydrogen evolution catalyst according to claim 1, characterized in that: Firstly, a metal precursor is loaded on nickel foam and phosphated to obtain a phosphide catalyst; then the catalyst surface is treated to obtain a phosphide hydrogen evolution catalyst with a phosphorus oxide protective layer.

3. The preparation method according to claim 2, characterized in that: The specific steps of this method are as follows: (1) The nickel foam was treated with 1 mol∙L -1 acetone, hydrochloric acid solution and deionized water, and dried for later use; (2) Mixing a Ni source and a Co source with NH4F, urea and deionized water to form a uniform solution, wherein the molar ratio of Co to Ni is 1-2:1, the molar ratio of NH4F to Co is 4-8:1, the molar ratio of urea to Co is 10-20:1, and the molar ratio of Co to deionized water is 0.001-0.002:1, transferring the solution to a reactor containing a vertically placed nickel foam, performing a hydrothermal reaction at 120-160° C. for 6-12 hours, cooling to room temperature, washing the solution alternately with ethanol and deionized water for 3 times, and drying the solution to obtain a catalyst precursor; (3) The catalyst precursor and P source were placed in two quartz boats respectively, with the molar ratio of P source to Ni source being 3-6:

1. The quartz boats were then placed in a tube furnace and phosphated at 350 °C for 2 h in an inert gas atmosphere at a heating rate of 2 °C∙min. -1 , phosphating treatment is performed to obtain a NiCoP hydrogen evolution catalyst; (4) After the temperature of the tube furnace is lowered to 50-100°C, the air valve is opened and the oxygen content in the inert gas is adjusted to 0.5-10 v%. The treatment time is 1-2 hours and the temperature is lowered to room temperature to obtain NiCoP@Ni x Co y P z O h Hydrogen evolution catalyst.

4. The preparation method according to claim 3, characterized in that: The Ni source is any one of nickel chloride, nickel nitrate and nickel acetate.

5. The preparation method according to claim 3, characterized in that: The Co source is any one of cobalt chloride, cobalt nitrate and cobalt acetate.

6. The preparation method according to claim 3, characterized in that: The P source is any one of ammonium hypophosphite and sodium hypophosphite.

7. The preparation method according to claim 3, characterized in that: In step (4), the inert gas is N2 gas or Ar gas.

Citation Information

Patent Citations

  • Foamed nickel self-supporting FeCo phosphide electrocatalyst, preparation method and application thereof

    CN112774704A

  • Fe-Co bimetallic phosphide electrode material and preparation and application thereof

    CN112941559A

  • Preparation method of O-doped NiCoP efficient hydrogen evolution electrode

    CN113278988A

  • Preparation method and application of foamed nickel loaded nitrogen phosphorus oxygen / nickel phosphide flower-like material

    CN114774957A